New records of leaf-mining Tortricidae (Lepidoptera) in North America, with the description of a new species of Grapholita - Eiseman, Charles S.; Austin, Kyhl A.; Blyth, Julia A.; Feldman, Tracy S. (Zootaxa, 2020)
We discuss seven species of tortricid moths that are leafminers at least in early instars. These include Grapholita thermopsidis Eiseman & Austin, new species, which feeds on Thermopsis rhombifolia (Pursh) Richardson (Fabaceae), along with two others for which larval hosts were previously unknown: Catastega triangulana Brown (Ericaceae: Arctostaphylos pungens Kunth) and Sparganothis xanthoides (Walker) (Polemoniaceae: Phlox divaricata L.). Parasitoids of G. thermopsidis include Dolichogenidea sp. (Hymenoptera: Braconidae) and Zagrammosoma mirum Girault (Hymenoptera: Eulophidae). The female genitalia of Epinotia nigralbana (Walsingham), a species that mines leaves of Arctostaphylos throughout larval development, are illustrated for the first time. Rhopobota finitimana (Heinrich), which feeds on Ilex spp. (Aquifoliaceae), is confirmed to mine leaves as has been documented previously in R. dietziana (Kearfott). Talponia plummeriana (Busck), which is known to feed in the developing ovaries of pawpaw (Annonaceae: Asimina spp.), also feeds in leaves before boring in the twigs and stems. Cenopis lamberti (Franclemont), previously reported from Persea sp. (Lauraceae), was reared from Symplocos tinctoria (L.) L’Hér. (Symplocaceae). Apart from the two exceptions noted above, all of these species exit their mines in later instars to feed in leaf shelters.